2009
DOI: 10.1175/2008jpo3954.1
|View full text |Cite
|
Sign up to set email alerts
|

Tilted Baroclinic Tidal Vortices

Abstract: The structure of baroclinic vortices generated by horizontal flow separation past a sloping headland in deep, stably stratified waters is investigated. The most distinctive feature of these eddies is that their cores are strongly tilted with respect to the stratification, yet their velocity field remains quasi-horizontal. Field observations and numerical simulations are used to explore the consequences of the strong tilt on the eddy baroclinic structure. It is found that the background density field is altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Canals et al . [] show that the velocity remains almost entirely horizontal. TTP is not the only place to spawn tilted eddies.…”
Section: Physical Mechanisms That Create Form Dragmentioning
confidence: 99%
See 1 more Smart Citation
“…Canals et al . [] show that the velocity remains almost entirely horizontal. TTP is not the only place to spawn tilted eddies.…”
Section: Physical Mechanisms That Create Form Dragmentioning
confidence: 99%
“…[], who details its time evolution, and by Canals et al . [], who describe the isopycnal structure resulting from the eddy tilt. The form drag at TTP is as much as 50 times larger than frictional drag over a flat bottom of equivalent area [ Edwards et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Precise bottom pressure sensors (Ppods) (St€ ober and Moum 2011) were deployed across the bathymetry near Three Tree Point (TTP), a headland in Puget Sound, Washington, with predictable tidal currents. TTP has been studied extensively in the past: Edwards et al (2004) and McCabe et al (2006) quantified the internal and external form drag, respectively, Canals et al (2009) described the tilted eddies present there, and Warner and MacCready (2009, hereafter WM09) showed with a numerical model that there is an additional part of the form drag that arises in oscillatory flow situations (''inertial'' form drag). In this study, total form drag from bottom pressure sensors, ''bulk'' drag estimated from the shallow water momentum equation, internal form drag, inertial form drag (arising from tidal time-dependence), frictional drag, and turbulent dissipation are all quantified.…”
Section: Introductionmentioning
confidence: 99%
“…At peak floods, the spatially integrated dissipation is only 25%-50% of the total power. Assuming that our turbulence observations have adequately captured the total dissipation, this suggests that not all of the energy is dissipated locally, but instead is carried away from the topography by either eddies (McCabe et al 2006;Canals et al 2009) or internal waves (section 5a) that do not break directly above TTP. The percentage of local energy dissipation at TTP can be compared to other sites such as Knight Inlet where Klymak and Gregg (2004) found that one-third of the energy lost (Fig.…”
mentioning
confidence: 95%
“…This is in agreement with the new unstable mode found by Candelier, Le Dizès & Millet (2011) in a tilted jet using a linear stability analysis. The existence of tilted vortices in a strongly stratified fluid is made possible because the streamlines remain horizontal but centred around a tilted axis (Boulanger, Meunier & Le Dizès 2006;Canals, Pawlak & MacCready 2009). However, this structure generates a critical layer at the radius where the angular velocity equals the Brunt-Väisälä frequency, leading to strong axial shears which are unstable with respect to the Kelvin-Helmholtz instability (Boulanger, Meunier & Le Dizès 2007).…”
Section: Introduction and Contextmentioning
confidence: 99%